2018
DOI: 10.5588/pha.17.0085
|View full text |Cite
|
Sign up to set email alerts
|

Integration of tobacco cessation and tuberculosis management by NGOs in urban India: a mixed-methods study

Abstract: The authors express their sincere thanks to all the patients, all the DOTS providers and staff of the three non-governmental organisations (Maharashtra Janavikas Kendra, Lok Seva Sangam and Peoples Association for Training and Health, Mumbai, India) for their participation in the study, and M D'Costa for her help in data collection. The training programme and open access publication costs were funded by the Department for International Development (London, UK), The Union, MSF and La Fondation Veuve Emile Metz-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…The most frequently described facilitators that foster smoking cessation/TDT in TB patients were repeated brief interventions (including motivation and brochures) 15 - 17 , 28 , 31 followed by personalized behavioural counselling incorporated into routine TB services 24 , 35 , 43 , 46 . The SCIDOT project showed that adding smoking cessation intervention (SCI) to conventional DOTS increased biochemically validated 6-month abstinence 24 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequently described facilitators that foster smoking cessation/TDT in TB patients were repeated brief interventions (including motivation and brochures) 15 - 17 , 28 , 31 followed by personalized behavioural counselling incorporated into routine TB services 24 , 35 , 43 , 46 . The SCIDOT project showed that adding smoking cessation intervention (SCI) to conventional DOTS increased biochemically validated 6-month abstinence 24 .…”
Section: Resultsmentioning
confidence: 99%
“…*** *** Living in urban areas, office jobs, being single significantly increased the intention to quit smoking 22 Combined interventions 13,19,20 Brief, but repeated interventions, motivation, brochures [15][16][17]28,31 Tobacco-free healthcare facilities 25 Time from waking to first cigarette of >30 min, routine screening for smoking, having a smoke-free home and display of 'no smoking' sign at home, regular reminders and encouragement of by family members to quit smoking 25 Willingness to quit -higher in those with previous attempt(s) in the past year 32 Incorporating of training in brief advice into existing training of DOTS providers 33 Personalized behavioural counselling incorporated into routine TB services 24,35,43,46 High level of awareness regarding smoking risk for health 36 Multiple risk behaviour interventions 37 Repeated tobacco use intervention follow-up at a minimum of 6 months after end of TB treatment 30,43 Providing intervention not only at a health facility but also on a daily basis at community level by health volunteers 46…”
Section: Facilitators Of Smoking Cessation/tdt In Patients With Tb Ofmentioning
confidence: 99%
“…These findings on the importance of images are in line with prior research on BCT-based cessation interventions in South Asia. 1618 Patients were not opposed to being approached about their smoking habit, although health workers expressed concerns that women might not admit to tobacco use and that asking about tobacco use was a sensitive issue. 12 There is a need for more in-depth research on what role stigma really plays and whether gender remains a determinant for smoking even among younger generations of women in Bangladesh and Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…To address these challenges, support from National TB Programmes and clinic heads to reduce documentation burden and ensure regular refresher training seems to be essential, as has been shown elsewhere. 18…”
Section: Discussionmentioning
confidence: 99%
“…[ 28 ] Studies in India have also found the integration of tobacco cessation services provided by DOTs providers in routine care to be feasible and effective. [ 29 30 31 ] Regular monitoring of TB patients of tobacco use and nicotine dependence can also be tried to formulate a tailored tobacco cessation plan for patients. One of the limitations of the study was the assessment of tobacco use which was self-reported by the patients; this could have led to an underestimation of the prevalence of tobacco use among TB patients due to the social desirability bias.…”
Section: Discussionmentioning
confidence: 99%